Simulations of the behavior of a pipeline made from three different types of materials on a landslide - Kowalska-Kubsik, Iwona (Wydawnictwa AGH, 2024)
The study presents numerical analyses of the behavior of pipelines made from various materials (steel, polypropylene, composite) under landslide conditions. Landslides are phenomena most commonly occurring in foothill and mountainous areas, and pipelines located on slopes can sustain damage during the landslide process. To determine the nature and extent of potential damage, numerical simulations were conducted based on advanced computational methods. The analysis employed the Drucker-Prager constitutive soil model. Numerical analyses make it possible to determine the deformation and stress states in pipelines without the need for costly experimental studies. By comparing simulation results for different materials, it is possible to assess the suitability of various pipes for placement on slopes.
Journal of Geotechnology and Energy
Keywords: numerical simulation; landslide; gas pipe; materials